(untitled) (Journal of the College of Basic Education, 2024)
Since time immemorial most world countries suffered from divers diseases that affected people’s life which lead ,to death . But with the passage of time and the growth of science and technology, there has become an imperative need to awareness people about diseases, their spread and ways to prevent diseases. One of the most important medical awareness tools that have emanated lately are medical posters, which depend on convey medical information to different segments of society in simple and understandable way, by blending between written words, phrases ,images or illustrations to be more attractive and more convincing. Many tools are used in medical posters give increase to some controversy over their ideologies, which used to convey the purpose of medical posters, this study aims to critically investigate of how posters are used to reveal thoughts and strategies of the designer in order to convey meaning and convincingness people. which try to answers to the subsequent research questions: What are the major elements employed in English medical posters ? What are the ideologies carry in English medical posters? And how are medical tips portray as an images in English medical posters in general? This paper hypothesis that medical posters depend on Extra -linguistic tools in to send their messages and persuades people with medical tips over and above linguistic elements . the selecting data depend on three samples of English medical posters choosing from :Freepik ,World Health Organization and ISWAN .The posters analyzed in consideration of an selected model Van Dijk (2000) and Kress and Van Leuween (2006). The results of analysis show that designers of medical posters constructed the intended messages by employ both linguistic and Extra -linguistic elements, but they tend to depend more on Extra -linguistic elements. The results also demonstrate that people are more convinced via extra-linguistic elements specially on colors, illustrations and gaze, while the speakers tend to formulate their ideologies mainly via linguistic elements. Also the study shows how the designer of English medical poster portrays medical tips as an images by using appropriate design to guide audience through the information, create something eye catching, but easy to read. Design the center of medical poster to offer something visually interesting important medical tips image , or a schematic of the medical information. These results verify the aims of the study.